Cone-beam computed tomography in implant dentistry - guidelines, current concepts and limitations for practice - Zuzanna Popińska; Daniel Ślusarczyk; Bartłomiej Żmuda; Wiktoria Jakubowska; Piotr Pisera; Aleksandra Kiełkowicz; Michał Żuberek; Filip Pactwa (Kazimierz Wielki University, 2024)
This article issues scientific background of Cone-beam computed tomography (CBCT) and the importance of taking x-rays before and after implant placement in daily practice as a common care. The review will introduce cone-beam computed tomography guidelines, restrictions and intraoperartive issues for instance nerve damage and bleeding incidents. Modern CBCT technology enables specialists to avoid making a wrong diagnosis, which translates into a higher percentage of people with a positive treatment outcome. Diagnostic radiology is a crucial element of every dental treatment planning. CBCT market is expanding gradually since two decades, there are more than 85 distinct CBCT tools available. CBCT is a three-dimensional (3D) imaging used nowadays in dentistry with increased frequency and offers volumetric data on jaw bones and teeth with relatively low radiation doses and costs. Currently, the greatest advantage of CBCT examinations over radiographs is the fact that the image obtained is presented in a 3D projection and not, as is the case, in 2D. It has the ability to help a wider range of patients, but the use of CBCT also has negative consequences. Routine or excessive use has resulted in increased radiation doses accumulating in the patient's body, which translates into an increased risk of adverse effects. The risk varies according to the age of the patient under study and is directly proportional to it, that is, it is highest for young people and lower for older people. The potential risk is also slightly higher in the female population. For this reason, creating awareness of the mandatory patient safety management of CT scans is a key process by which X-ray exposures can be optimised.